Immuno-PET Imaging of Siglec-15 Using the Zirconium-89-Labeled Therapeutic Antibody, NC318 - Elaine M. Jagoda; Falguni Basuli; Colleen Olkowski; Ido Weiss; Tim E. Phelps; Karen Wong; Anita Thien Ton; Kelly C. Lane; Steve Adler; Donna Butcher; Elijah F. Edmondson; Sol Langermann; et al. (Molecular Imaging)
Objective. Sialic acid-binding immunoglobulin-like lectin 15 (Siglec-15) is overexpressed in various cancers which has led to the development of therapeutic anti-Siglec-15 monoconal antibodies (mAbs). In these preclinical studies, the therapeutic mAb, NC318 (antihuman/murine Siglec-15 mAb), was labeled with zirconium-89 and evaluated in human Siglec-15 expressing cancer cells and mouse xenografts for potential use as a clinical diagnostic imaging agent. Methods. Desferrioxamine-conjugated NC318 was radiolabeled with zirconium-89 to synthesize [89Zr]Zr-DFO-NC318. Cancer cell lines expressing variable Siglec-15 levels were used for in vitro cell binding studies and tumor xenograft mouse models for biodistributions. [89Zr]Zr-DFO-NC318 biodistribution and PET imaging studies to determine tissue uptakes (tissue : muscle ratios, T : M) included pharmacokinetic evaluation in Siglec-15+tumor xenografts and immunocompetent mice, blocking with nonradioactive NC318 (20, 100, and 300 μg) and xenografts with low/negligible Siglec-15 expressing tumors. Results. [89Zr]Zr-DFO-NC318 exhibited high affinity (Kd~4 nM) for Siglec-15 and distinguished between moderate and negligible Siglec-15 expression levels in cancer cell lines. The highest [89Zr]Zr-DFO-NC318 uptakes occurred in the spleen and lymph nodes of the Siglec-15+tumor xenografts at all time points followed by Siglec-15+tumor uptake which was lower although highly retained. In immunocompetent mice, the spleen and lymph nodes exhibited lower uptakes indicating that the athymic xenografts had increased Siglec-15+ immune cells. Specific [89Zr]Zr-DFO-NC318 binding to Siglec-15 was proven with NC318 blocking studies in which dose-dependent decreases in Siglec-15+tumor T : Ms were observed. Higher than expected, tumor T : Ms were seen in lower expressing tumors likely due to the contribution of murine Siglec-15+ immune cells in the tumor microenvironment as confirmed by immunohistochemistry. Siglec-15+tumors were identified on PET images whereas low/negligible expressing tumors showed lower uptakes. Conclusions. In vitro and in vivo [89Zr]Zr-DFO-NC318 uptakes correlated with Siglec-15 expression levels in target tissues. Despite uptake in immune cell subsets in the tumor microenvironment, these results suggest that clinical [89Zr]Zr-DFO-NC318 PET imaging may have value in selecting patients for Siglec-15-targeted therapies.